2022
DOI: 10.20473/jn.v17i1.31216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress, anxiety, and depression with suicidal ideation in adolescents

Abstract: Introduction: Suicide is a significant mental health problem in adolescents around the world that requires comprehensive treatment. This study aimed to examine the relationship between stress, anxiety, and depression with suicidal ideation in adolescents. Method: This research used quantitative methods with a cross-sectional approach. The number of respondents was 869 adolescents, with a total sampling technique. The instrument used to measure stress, anxiety, and depression is the Depression Anxiety Stress Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…56 Therefore, it is crucial to identify anxiety and depression and the related factors due to them having worse consequences on mental health, such as suicidal behavior. 57 Although the present study employed a valid instrument for data gathering, the limitation of this study was the recruitment process. Approximately 5% of the respondents did not complete the questionnaire fully since it was an online survey.…”
Section: Discussionmentioning
confidence: 94%
“…56 Therefore, it is crucial to identify anxiety and depression and the related factors due to them having worse consequences on mental health, such as suicidal behavior. 57 Although the present study employed a valid instrument for data gathering, the limitation of this study was the recruitment process. Approximately 5% of the respondents did not complete the questionnaire fully since it was an online survey.…”
Section: Discussionmentioning
confidence: 94%
“…The cut-off points for anxiety were 0–7 (normal), 8–9 (mild), 10–14 (moderate), 15–19 (high) and >20 (very high). The cut-off points for stress were 0–14 (normal), 15–18 (mild), 19–25 (moderate), 26–33 (high) and >34 (very high) [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety disorders among adolescents also cause an increased risk for suicidal behavior ( 3 ). In a study by Windarwati et al ( 4 ) among 869 high school adolescents, 72.7% of teens experienced anxiety in the mild to very severe categories. The study also showed a significant relationship between suicidal ideation with anxiety in adolescents.…”
Section: Introductionmentioning
confidence: 96%